Roadway support material taking high-temperature smelting slag and gypsum as raw materials and preparation method of roadway support material

By combining high-temperature smelting slag with industrial by-product gypsum, a modified cementitious material was prepared, which solved the problems of fast material coagulation, high early strength, waterproof and corrosion resistance in the tunnel support environment, and achieved efficient utilization of industrial solid waste, which was suitable for the preparation of tunnel support materials.

CN119797873APending Publication Date: 2025-04-11CHINA TIN NONFERROUS METALS CO LTD +1

Patent Information

Application Number
CN202411960424.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to provide materials with fast condensation, high early strength, waterproof and corrosion-resistant in tunnel support environments, and the utilization rate of industrial solid waste is not high.

Method used

Using high-temperature smelting slag and industrial by-product gypsum as raw materials, a new tunnel support material is prepared by combining modified cement cementitious materials and fillable aggregates. The material includes high-temperature smelting slag, industrial by-product gypsum, rare earth exciters, ordinary cement, water reducing agents and defoaming agents. Through a specific weight ratio and stirring process, a supporting material with high compressive strength and corrosion resistance is formed.

Benefits of technology

The rapid condensation and early high strength of the tunnel support material are achieved, with an initial settling time of 1.5 minutes and a final settling time of 4 minutes. The compressive strength is not less than 11MPa in 1 d. The compressive strength is stable after 14 d. The compressive strength retention rate is 100% in 90 d. At the same time, it has good sulfate corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a roadway support material taking high-temperature smelting slag and gypsum as raw materials. The roadway support material comprises a modified cement binding material and a filling aggregate which are mixed according to the weight ratio of 1: (0.35-0.68). The invention also discloses a preparation method of the roadway support material, which comprises the following steps of: putting the high-temperature smelting slag, the industrial byproduct gypsum, the rare earth exciting agent and the cement into a stirrer according to the weight ratio, stirring for 5-30 minutes at the speed of 100-500r / min, then putting at the constant temperature of 90-150 DEG C for 0.5-2 hours, cooling to room temperature, and uniformly mixing with the water reducing agent and the defoaming agent according to the weight ratio to obtain the modified cement cementing material. The utilization rate of the high-temperature smelting slag reaches 5.5%-11.2%, the utilization rate of the industrial byproduct gypsum reaches 4%-6%, it is still guaranteed that the industrial solid waste has the good utilization rate on the premise that a suitable roadway supporting material is prepared, and a new way is provided for protecting the ecological environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of mine tunnel support, and in particular relates to a tunnel support material using high-temperature smelting slag and gypsum as raw materials and a preparation method thereof. Background Art

[0002] High-temperature smelting slag includes steelmaking quenching slag and non-ferrous metal smelting slag such as tin, lead, zinc, and antimony. Steelmaking quenching slag refers to the molten blast furnace slag, which is a sand-like glassy substance obtained by rapid cooling of a water or air mixture. Tin, lead, zinc, and antimony non-ferrous metal smelting slag is the solid waste discharged during the smelting process of non-ferrous metals, including FeO, Fe 2 O 3 、SiO 2 、SnO、CaO、MgO、ZnO、Al 2 O 3 , Sb 2 O 3 In addition, it also contains sulfides and a small amount of metals. Industrial by-product gypsum refers to the by-product or waste residue with calcium sulfate as the main component generated by chemical reactions in industrial production, also known as chemical gypsum or industrial waste gypsum. It mainly includes desulfurized gypsum, phosphogypsum, citric acid gypsum, fluorinated gypsum, salt gypsum, monosodium glutamate gypsum, copper gypsum, titanium gypsum, etc.

[0003] At present, we have found the following patents for the utilization of industrial solid waste: 1. Application No. 202010497341.X, Invention Name: A method and process for repairing concrete cracks in road and bridge construction. The concrete crack repair material in road and bridge construction is made of the following raw materials in parts by mass: 30-60 parts of aluminum sulfate cement, 15-25 parts of high alumina cement, 5-10 parts of alum stone, 5-12 parts of limestone, 8-15 parts of slag, 10-15 parts of fine sand, 5-10 parts of calcium stone powder, 1-3 parts of water reducer, 1-2 parts of rubber powder, 3-8 parts of desulfurized gypsum, 3-8 parts of unsaturated polyester resin, 2-6 parts of titanate coupling agent, 2-8 parts of nano titanium dioxide, 1-2 parts of vinyl triethoxy silane, 1-2 parts of cellulose ether, 2-4 parts of retarder, 2-5 parts of tackifying resin, 1-2 parts of leveling agent, 1-3 parts of hydroxypropyl methylcellulose, and 15-25 parts of pure water. The invention has a high utilization rate of industrial solid waste, but its materials are added with high-aluminum cement, which is the most important type of aluminate cement system and has the characteristics of fast hardening and early strength. High-aluminum cement uses alumina and lime as raw materials and is also called alumina cement. The use of high-aluminum cement will produce the problem of strength shrinkage in the later stage. After 3 to 5 years of use, the strength of high-aluminum cement concrete is only half of the early strength. It is generally not suitable for permanent load-bearing structural engineering and is not suitable for large-scale concrete engineering. Therefore, it is mainly used for road and bridge repairs and is not suitable for special tunnel support environments.

[0004] 2. Application No. 201911384734.3, Invention Name: A kind of phosphogypsum solid waste foamed concrete, which includes the following raw materials in parts by weight: 50-70 parts of phosphogypsum, 10-20 parts of ordinary Portland cement, 40-50 parts of slag, 20-30 parts of modified bentonite, 10-20 parts of activated carbon nanotubes, 1-2 parts of water reducer, 0.1-0.3 parts of foaming agent, 1-3 parts of foam stabilizer, 35-40 parts of coarse aggregate, 25-35 parts of fine aggregate, and 35-40 parts of water. Without considering the addition of water, the maximum addition ratio of phosphogypsum in this invention is 33.00%, and the maximum addition ratio of slag is 24.74%. This invention has a high utilization rate of phosphogypsum and slag, and its 28-day strength can reach 24.8MPa. However, the product foamed concrete of this invention is mainly used in the fields of sound absorption and sound insulation, thermal insulation, anti-seepage and waterproofing, fire resistance, and fire prevention. According to conventional understanding, the initial setting time of foamed concrete is 2-3 hours, and the final setting time is 24-48 hours. It is not resistant to acid corrosion. According to the requirements of the tunnel support environment for cement acid corrosion resistance and rapid setting and early strength, this product is not suitable for use in tunnel support. The same problem also exists in an ecological cementitious material prepared using lead-zinc slag and a preparation method thereof disclosed in Patent No. 202010289600.X. Summary of the invention

[0005] The purpose of the present invention is to solve the above technical problems and provide a tunnel support material with high solid waste utilization rate, fast coagulation, high early and late strength, waterproof and corrosion resistance, and a preparation method thereof using high-temperature smelting slag and gypsum as raw materials.

[0006] To achieve the above-mentioned purpose, the technical solution of the present invention is: A tunnel support material using high-temperature smelting slag and gypsum as raw materials, the tunnel support material comprising a modified cement binder and a filling aggregate mixed in a weight ratio of 1: (0.35-0.68), the modified cement binder comprising high-temperature smelting slag, industrial by-product gypsum, rare earth activator, ordinary cement, a water reducer and a defoamer, the weight ratio of the high-temperature smelting slag, industrial by-product gypsum, rare earth activator, ordinary cement, a water reducer and a defoamer being 1: (0.9-1): (0.008-0.01): (2-4): (0.01-0.025): (0.008-0.01) As a further technical solution, the high temperature smelting slag is any one of steelmaking quenching slag and tin, lead, zinc, antimony non-ferrous metal smelting slag or a mixture of more than one; the specific surface area of ​​the high temperature smelting slag is not less than 350m 2 / g.

[0007] As a further technical solution, the industrial by-product gypsum mentioned above is any one of desulfurized gypsum and phosphogypsum or a mixture of more than one of them.

[0008] As a further technical solution, the rare earth activator mentioned above is any one of cerium sulfate, cerium nitrate, cerium chloride, lanthanum sulfate, lanthanum nitrate and cerium chloride, or a mixture of more than one of them.

[0009] As a further technical solution, the ordinary cement mentioned above is any one of aluminum sulfate cement and aluminum silicate cement or a mixture of more than one of them.

[0010] As a further technical solution, the water reducer mentioned above is an early strength water reducer; the early strength water reducer is one or a mixture of more than one of calcium lignin sulfonate, sodium lignin sulfonate and magnesium lignin sulfonate.

[0011] As a further technical solution, the defoamer mentioned above is a polyether-modified silicon defoamer.

[0012] As a further technical solution, the filling aggregate mentioned above is one or a mixture of more than one of heavy calcium and quartz sand.

[0013] A method for preparing a tunnel support material using high-temperature smelting slag and gypsum as raw materials comprises the following steps: High-temperature smelting slag, industrial by-product gypsum, rare earth activator and ordinary cement are placed in a stirrer according to weight ratio and stirred at 100-500 rpm for 5-30 minutes, then placed at a constant temperature of 90°C-150°C for 0.5-2 hours, and after cooling to room temperature, mixed with a water reducer and a defoamer according to weight ratio to obtain a modified cement gelling material; the modified high-temperature smelting slag of the present invention can be better combined with a filling aggregate, thereby having a greater compressive strength.

[0014] The modified cement binder material and the filling aggregate are uniformly mixed in a weight ratio of 1: (0.35-0.68) to obtain a tunnel support material product.

[0015] The reaction mechanism of the present invention is: after adding water and stirring the tunnel support material product provided by the present invention, the connection between the high-temperature smelting slag rich in glass structure becomes tighter and more stable under the action of the rare earth activator; at the same time, the polyether modified silicon is hydrolyzed so that the whole system forms a dense silicon oxygen-aluminum-calcium-rare earth element composite film, so that the support material obtains higher compressive strength and corrosion resistance after solidification. In addition, the rare earth activator can form a stable compound with the water reducer lignin sulfonate, which helps the water reducer to improve the early strength performance of the support material.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The product of the present invention has the advantages of fast setting, high early and late strength, and waterproof and corrosion resistance. Traditional cement materials will corrode and peel off in acidic organic soils for a long time, and it is difficult to meet the needs of working in a low pH environment for a long time. At the same time, the setting time of traditional cement is too long, and it is not suitable for closed and humid tunnel environments. Without the need to add high-alumina cement, the weight ratio is limited by the present invention, and the initial setting time of the product is 1.5 minutes and the final setting time is 4 minutes, which can achieve rapid setting; not only that, the product of the present invention has high early strength, the 1d compressive strength is not less than 11MPa, and the compressive strength is stable after 14d, both are not less than 22MPa, and the 90d compressive strength retention rate is 100%, which can achieve an ideal tunnel support effect; in addition, the 28d sulfate erosion resistance coefficient of the product of the present invention is 1.05, which means that the product of the present invention can maintain stable performance in harsh environments. In summary, the product of the present invention is particularly suitable for tunnel support materials, which are mixed with water at a weight ratio of 1:0.18-0.26 for 5-30 minutes to form a slurry, which is then sprayed on the tunnel by a spraying device to support the tunnel.

[0017] 2. The present invention achieves a utilization rate of 5.5% to 11.2% for high-temperature smelting slag and a utilization rate of 4% to 6% for industrial by-product gypsum. On the premise of preparing suitable tunnel support materials, it still ensures that industrial solid waste has a good utilization rate, providing a new way to protect the ecological environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a compressive strength test report diagram of the mortar test block 1d of Example 1 of the present invention; Figure 2 This is a compressive strength test report diagram of the mortar test block 3d of Example 1 of the present invention; Figure 3 This is a compressive strength test report diagram of the mortar test block 7d of Example 1 of the present invention; Figure 4 This is a compressive strength test report diagram of the mortar test block 14d of Example 1 of the present invention. DETAILED DESCRIPTION

[0019] The present invention is further described in detail below in conjunction with examples, but the implementation mode of the present invention is not limited to the scope represented by the examples.

[0020] The high-temperature smelting slag in the embodiment of the present invention comes from the smelting slag after roasting in a rotary kiln of a tin polymetallic mine of a tin industry in Guangxi Zhuang Autonomous Region and the high-temperature water slag of a steel company in Guangxi Zhuang Autonomous Region.

[0021] Embodiment 1:

[0022] 1990 g of ordinary aluminum sulfate cement was placed in a mixing tank and a specific surface area of ​​400 m2 / g, 630g of tin-antimony nonferrous metal smelting slag, 100 mesh, 630g of phosphogypsum and 6g of cerium nitrate hexahydrate, stirred at 325 rpm for 15min, then kept at 110°C for 0.5h, and after cooling to room temperature, placed in a stirring tank with 9g of calcium lignin sulfonate and 6g of polyether modified silicon defoamer and mixed at 325 rpm for 15min to obtain modified cement gelling material. Subsequently, the obtained modified cement gelling material was stirred with 3000g of quartz sand at 325 rpm for 20min to obtain support material gel powder. The obtained support material gel powder was placed in a stirring container, 1200g of water was added, and stirred at 300 rpm for 10min to obtain tunnel support material slurry. The obtained slurry was poured into a standard model of 70.7mm×70.7mm×70.7mm, compacted, placed at room temperature for curing, and handed over to the demander of tunnel support materials for relevant evaluation. Figure 1-4 As shown, the experimental performance is characterized by: initial setting time 1.5 min, final setting time 4 min, 1d compressive strength 11.7 MPa, 3d compressive strength 16.5 MPa, 7d compressive strength 22.4 MPa, 14d compressive strength 22.8 MPa, 90d compressive strength retention rate is 100%, and 28d sulfate erosion resistance coefficient is 1.05.

[0023] Embodiment 2:

[0024] 1900g of ordinary aluminum sulfate cement was placed in a mixing tank and a specific surface area of ​​400 m 2 / g, 700g of steelmaking quenched slag, 100 mesh, 650g of phosphogypsum and 6.6g of cerium chloride, stirred at 325 rpm for 15min, then placed at 110℃ for 0.5h, and after cooling to room temperature, placed in a stirring tank with 8.6g of sodium lignin sulfonate and 5.8g of polyether modified silicon defoamer and mixed at 325 rpm for 15min to obtain a modified cement gelling material. Subsequently, the obtained modified cement gelling material was stirred with 3000g of heavy calcium at 325 rpm for 20min to obtain a support material gel powder. The obtained support material gel powder was placed in a stirring container, 1200g of water was added, and stirred at 300 rpm for 10min to obtain a tunnel support material slurry. The obtained slurry was poured into a standard model of 70.7mm×70.7mm×70.7mm, compacted, placed at room temperature for curing, and relevant evaluations were performed. The experimental performance is characterized by: initial setting time 1.5 min, final setting time 4 min, 1d compressive strength 14.2 MPa, 3d compressive strength 17.3 MPa, 7d compressive strength 24.9 MPa, 14d compressive strength 25.4 MPa, 90d compressive strength retention rate is 100%, and 28d sulfate erosion resistance coefficient is 1.05.

[0025] Embodiment 3:

[0026] 1990 g of ordinary aluminum silicate cement was placed in a mixing tank and a specific surface area of ​​400 m 2 / g, 630g of steelmaking quenched slag, 100 mesh, 630g of desulfurized gypsum and 6g of lanthanum nitrate were stirred at 325 rpm for 15min, then placed at 110℃ for 0.5h, and after cooling to room temperature, 9.3g of magnesium lignin sulfonate and 6.2g of polyether modified silicon defoamer were placed in a stirring tank and mixed at 325 rpm for 15min to obtain a modified cement gelling material. Subsequently, the obtained modified cement gelling material was stirred with 3000g of quartz sand at 325 rpm for 20min to obtain a support material gel powder. The obtained support material gel powder was placed in a stirring container, 1200g of water was added, and stirred at 300 rpm for 10min to obtain a tunnel support material slurry. The obtained slurry was poured into a standard model of 70.7mm×70.7mm×70.7mm, compacted, placed at room temperature for curing, and relevant evaluations were performed. The experimental performance is characterized by: initial setting time 1.5 min, final setting time 4 min, 1d compressive strength 11.1 MPa, 3d compressive strength 15.7 MPa, 7d compressive strength 21.6 MPa, 14d compressive strength 22.3 MPa, 90d compressive strength retention rate is 100%, and 28d sulfate erosion resistance coefficient is 1.05.

[0027] The above embodiments are only specific examples for further describing the purpose, technical solutions and beneficial effects of the present invention, and the present invention is not limited thereto. Any modification, equivalent replacement, improvement, etc. made within the scope disclosed by the present invention are included in the protection scope of the present invention.

Claims

1. A tunnel support material using high-temperature smelting slag and gypsum as raw materials, characterized in that: The tunnel support material includes modified cement binder and filling aggregate mixed in a weight ratio of 1: (0.35-0.68), wherein the modified cement binder includes high-temperature smelting slag, industrial by-product gypsum, rare earth activator, ordinary cement, water reducer and defoamer, and the weight ratio of the high-temperature smelting slag, industrial by-product gypsum, rare earth activator, ordinary cement, water reducer and defoamer is 1: (0.9-1): (0.008-0.01): (2-4): (0.01-0.025): (0.008-0.01).

2. The tunnel support material with high temperature smelting slag and gypsum as raw materials according to claim 1 is characterized in that: The high-temperature smelting slag is any one of steelmaking quenching slag and tin, lead, zinc, antimony non-ferrous metal smelting slag or a mixture of more than one; the specific surface area of ​​the high-temperature smelting slag is not less than 350m 2 / g.

3. The tunnel support material with high temperature smelting slag and gypsum as raw materials according to claim 1 is characterized in that: The industrial by-product gypsum is any one of desulfurized gypsum and phosphogypsum or a mixture of more than one of them.

4. The tunnel support material with high temperature smelting slag and gypsum as raw materials according to claim 1 is characterized in that: The rare earth activator is any one of cerium sulfate, cerium nitrate, lanthanum sulfate, lanthanum nitrate and cerium chloride, or a mixture of more than one of them.

5. The tunnel support material with high temperature smelting slag and gypsum as raw materials according to claim 1 is characterized in that: The ordinary cement is any one of aluminum sulfate cement and aluminum silicate cement or a mixture of more than one of them.

6. The tunnel support material with high temperature smelting slag and gypsum as raw materials according to claim 1, characterized in that: The water reducer is an early strength water reducer; the early strength water reducer is one or a mixture of more than one of calcium lignin sulfonate, sodium lignin sulfonate and magnesium lignin sulfonate.

7. The tunnel support material with high temperature smelting slag and gypsum as raw materials according to claim 1 is characterized in that: The defoamer is a polyether modified silicon defoamer.

8. The tunnel support material with high temperature smelting slag and gypsum as raw materials according to claim 1 is characterized in that: The filling aggregate is one or a mixture of two or more of heavy calcium and quartz sand.

9. The method for preparing a tunnel support material using high temperature smelting slag and gypsum as raw materials according to any one of claims 1 to 8, characterized in that: The steps include: (1) placing high-temperature smelting slag, industrial by-product gypsum, rare earth activator and ordinary cement in a stirrer at a speed of 100 to 500 revolutions per minute for 5 to 30 minutes, then placing at a constant temperature of 90°C to 150°C for 0.5 to 2 hours, and after cooling to room temperature, mixing with a water reducing agent and a defoaming agent in a weight ratio to obtain a modified cementitious material; (2) The modified cement binder and the filling aggregate are uniformly mixed according to a weight ratio to obtain a tunnel support material product.

Citation Information

Patent Citations

  • An eco-friendly cementitious material prepared from lead-zinc slag and its preparation method

    CN111302741B

  • Concrete crack repairing method and process in road and bridge construction

    CN111470835A

  • Ardealite solid waste foam concrete and preparation method thereof

    CN113045331A

Cited By

  • Gelling base material for mine filling and capable of improving mixing amount of mineral separation tailings and filling material of cementing base material

    CN121800499A